Banking sector in Malaysia: pre and post merger / Atiqah Nabila Azman - Azman, Atiqah Nabila (2018)
As a solution for the Asian financial crisis in 1997, countries under International Monetary Fund (IMF) programmes are obliged to close down the small and weakest banking institution. However, Malaysia government has opposed the idea and come out with bank merger programme where all the 54 financial institutions were restructured into ten anchor banks in 1999. Therefore, this study attempts to investigate the impact of mergers and acquisition on the profitability of local banks in Malaysia during pre-merger and post-merger. This paper will examine the impact of merger on bank's profitability in terms of liquidity, leverage and firm size. Five years before the merger completed will consider as pre-merger period while five years after will treated as post-merger period. This study applies Multiple Regression Analysis with panel data. Banks data will be collected from bank's financial report on Datastream system. This research will highlight on eight anchor banks from the period of 1999 until 2011 and E-views will be used as a tool to run the regression analysis. This study expects that there will be positive relationship between total debt ratio, interest coverage ratio, current ratio and firm size on return on asset.